Physiological and unappreciated roles of CaMKII in the heart - Beckendorf, Jan; Hoogenhof, Maarten van den; Backs, Johannes (Basic research in cardiology, 2018)
In the cardiomyocyte, CaMKII has been identified as a nodal influencer of excitation-contraction and also excitation-transcription coupling. Its activity can be regulated in response to changes in intracellular calcium content as well as after several post-translational modifications. Some of the effects mediated by CaMKII may be considered adaptive, while effects of sustained CaMKII activity may turn into the opposite and are detrimental to cardiac integrity and function. As such, CaMKII has long been noted as a promising target for pharmacological inhibition, but the ubiquitous nature of CaMKII has made it difficult to target CaMKII specifically where it is detrimental. In this review, we provide a brief overview of the physiological and pathophysiological properties of CaMKII signaling, but we focus on the physiological and adaptive functions of CaMKII. Furthermore, special consideration is given to the emerging role of CaMKII as a mediator of inflammatory processes in the heart.
Gesehen am 09.03.2020